EFFECT OF DIFFERENT LIGHT REGIMENS ON PERFORMANCE OF BROILERS - A. Mahmud; Saima; Rafiullah; I. Ali (Journal of Animal and Plant Sciences, 2011)
In the present study the effect of different light regimen on the weight gain of broilers from 3rd to 6th week of age were studied (1) Continuous light (2) an intermittent system of 1 hr light and 2 hrs darkness at night with 11 hrs continuous light during the day (3) an intermittent system of 1 hr light and 3hrs darkness at night with 11 hrs continuous light during the day. All the birds were reared on continuous light until 2 weeks of age before the treatments were applied. Intermittent lighting system caused a significant (P<0.05) increase in the average weight gain as compared to continuous light. The weight gain in intermittent lighting of 1 hr light and 3hrs darkness was significantly (P<0.01) better than those of the continuous light and intermittent light of 1 hr light and 2 hrs darkness. Feed consumption of intermittent light of both group 2 and 3 was less than continuous light. The feed conversion ratio of intermittent light of groups 2 and 3 was significantly (P<0.05) better than continuous light.
Keywords: Broiler; Light regimens; intermittent light; growth; Feed consumption